Religious Experience of Jama'ah Mawlid Al-Diba Jamuna (Jamaat Muji Nabi) Girikusumo - Moh. Fahsin; Muhammad Arif, Iif (CV. Kalimasada Group, 2025)
In Indonesia, the spread of Islam has given rise to distinctive phenomena and traditions, largely due to its openness to external values, which has fostered assimilation and acculturation. This is evident in unique religious expressions such as the recitation of al-Diba'i, al-Barzanji, and Burdah, which reflect love and reverence for Prophet Muhammad and serve as a medium for seeking blessings and intercession. Despite the significance of these rituals for Indonesian Muslims, scientific research on their psychological and spiritual implications remains limited. This qualitative research employs a descriptive-analytical method, utilizing interviews, documentation, and observation to examine the tradition of al-Diba' recitation, particularly in Girikusumo, where the ceremony attracts thousands of participants weekly. While this tradition is often associated with certain Sufi Tariqahs, local practices emphasize community unification and da'wah rather than strict Tariqah affiliation. The active participation of youth in these events signals a revitalization of religious traditions, transcending generational boundaries. Participants are drawn to the practice for diverse reasons, ranging from spiritual pursuits to social networking, highlighting the broad appeal of the tradition. Most importantly, the recitation of Maulid al-Diba' fosters an egalitarian form of Islam, encouraging theological discourse across sectarian lines and reinforcing a Sufi Islamic identity that aligns with Indonesia’s cultural framework. This study concludes that, although not formally recognized as a Sufi ritual, the recitation of Maulid al-Diba' facilitates spiritual experiences, enriches religious consciousness, and strengthens individuals' connection to their faith and community.